Quantitation of α-Lactalbumin by Liquid Chromatography Tandem Mass Spectrometry in Medicinal Adjuvant Lactose - Rui Yan; Longmei Qu; Nan Luo; Yang Liu; Yu Liu; Li Li; Lijiang Chen (International Journal of Analytical Chemistry)
Lactose is a widely used pharmaceutical excipient, sometimes irreplaceable. Traces of residual proteins left during production of lactose are potential allergen to body. The present paper describes a sensitive and specific LC-MS method for the determination of α-lactalbumin (α-La) in lactose samples. Chromatographic separation was performed on an Acquity UPLC BEH300 C18 column (2.1×150 mm, 1.7 μm) with an isocratic mobile phase consisting of water containing 0.1% TFA and acetonitrile containing 0.1% TFA (80 : 20, v/v). Mass spectrometric detection was achieved by a triple-quadrupole mass spectrometer equipped with an ESI interface operating in positive ionization mode. Quantitation was performed using selected ion monitoring of m/z 2364 for α-La. The calibration curve was linear from 0.2 to 10 µg/mL. The intra- and interday precisions were less than 7.6% and the accuracy ranged from 96.4 to 104.5%. The limit of quantification (LOQ) was 0.15 µg/mL and the limit of detection (LOD) was 0.05 µg/mL. This method was then successfully applied to investigate 6 different lactose samples. The application can provide technical preparation for the development of specification of lactose.